2009
DOI: 10.1038/nnano.2009.293
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic control of ferroelastic switching in multiferroic materials

Abstract: Multiferroic materials showing coupled electric, magnetic and elastic orderings provide a platform to explore complexity and new paradigms for memory and logic devices. Until now, the deterministic control of non-ferroelectric order parameters in multiferroics has been elusive. Here, we demonstrate deterministic ferroelastic switching in rhombohedral BiFeO(3) by domain nucleation with a scanning probe. We are able to select among final states that have the same electrostatic energy, but differ dramatically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
354
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(386 citation statements)
references
References 38 publications
29
354
3
Order By: Relevance
“…While the (110) BFO shown in Figure 1a maintains a single-domain texture, the (100) BFO shown in Figure 1b exhibits striped domains lying along the o0104 direction with the two variants in the [110] and directions across the 711 or 1091 DWs. 13,14 Out-of-plane PFM measurements (not shown) confirmed that the out-of-plane components are pointing downward, that is, from the surface to the substrate. The rectangular device channels were defined by an electrode gap of 4 mm and a width of 30 mm by e-beam lithography and Au-electrode liftoff.…”
Section: Methodsmentioning
confidence: 79%
“…While the (110) BFO shown in Figure 1a maintains a single-domain texture, the (100) BFO shown in Figure 1b exhibits striped domains lying along the o0104 direction with the two variants in the [110] and directions across the 711 or 1091 DWs. 13,14 Out-of-plane PFM measurements (not shown) confirmed that the out-of-plane components are pointing downward, that is, from the surface to the substrate. The rectangular device channels were defined by an electrode gap of 4 mm and a width of 30 mm by e-beam lithography and Au-electrode liftoff.…”
Section: Methodsmentioning
confidence: 79%
“…In particular, they have predicted that flexoelectricity might be used to enhance pieozoelectric responses above bulk values. (ii) Recently, there have been many studies on the domains and domain walls of BiFeO 3 thin films owing to their scientific interest and potential applications [41,[51][52][53]. BiFeO 3 thin films with a monoclinic distortion undergo lattice deformation during polarization switching (i.e.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…8 As far as Scanning Probe Microscopy (SPM) is concerned, the recent developments in functional imaging-modes have been paralleled with a growing interest in studying various local phenomena. A few examples of such phenomena include electrical conduction at ferroelectric/ferroelastic domain walls, [9][10][11][12] polarization dynamics in ferroelectrics, [13][14][15][16][17][18] temperature/time/ voltage dependent study of ergodicity (time dependence) of polarization in relaxor-ferroelectrics, 14,19 and local magnetoelectricity. [20][21][22][23][24][25][26][27][28] Probing such local phenomena essentially requires measuring a response I ij (x i , P j ) on an X × Y grid, as a function of a spectral parameter P j (j = 1,…,M); where x i is the spatial coordinate index (i = 1,…,N; N = X × Y).…”
Section: Introductionmentioning
confidence: 99%